The Development of the Middle Class in Austria and Germany - Dénes Kucsera; Hanno Lorenz; Wolfgang Nagl (Wirtschaftsdienst)
Abstract We examine the changes and evolution of the middle class in Austria and Germany over the past 20 years. During that period, the middle class in Germany and Austria has changed in terms of education, family constellations and age. In both countries, however, a large part of the population still belongs to the middle class. In Austria, the percentage of people in the middle class appears to be stable and is slightly higher than in Germany. During the COVID-19 crisis, discretionary policy measures have been effective in limiting welfare losses for the middle class. Finally, we analyse the importance of the middle class for the welfare state of both countries.